Evolusi Pengaruh Budaya Jepang dalam Desain dan Gaya Berpakaian di Indonesia: Kajian Sistematis - Panjaitan, Lilis Lamsehat; Fatimah, Rezki (KIRYOKU, 2025)
This article aims to examine the evolution of Japanese cultural influence in design and fashion styles in Indonesia through a systematic review approach. Since the early 2000s, Japanese fashion trends have entered the Indonesian market, bringing unique and innovative design elements. This study aims to explore how these Japanese cultural elements are adapted and integrated into the local context, as well as their impact on the cultural identity of Indonesian society. Through an analysis of existing literature, it was found that fashion design students have begun to adopt Japanese cultural elements in their works and the adaptation of Japanese culture in contemporary fashion encompasses profound values. Additionally, the collaboration between batik motifs and kimono demonstrates the potential for innovation in fashion design, while social media plays a crucial role in disseminating these trends among the youth. Despite the numerous studies conducted, there remains a gap in systematic reviews regarding the evolution of Japanese cultural influence. Therefore, this article is expected to contribute new insights into the interaction between Japanese and Indonesian cultures in the context of fashion, as well as its implications for the creative industry and local cultural identity.